PERANAN BALAI BESAR PENGAWAS OBAT DAN MAKANAN DALAM MEMBERANTAS TINDAK PIDANA PEREDARAN OBAT KERAS DI SARANA YANG TIDAK MEMILIKI KEAHLIAN DAN KEWENANGAN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI PROVINSI RIAU - Mulyansyah, Handi; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Health development is carried out in various ways, one through the health service. In health care medicine is an important component because it is required in the majority of health efforts. Drugs are substances that are consumed the body to reduce pain and eliminate the disease. Drugs are usually manufactured in pharmaceutical companies with a chemical that has one advantage compared with traditional medicine, which is more sterile and kept clean. Hard drugs or medication list G (gevaarlijk) that is hard to obtain efficacious drugs should be by prescription. It is therefore hard drugs unregistered prohibited distributed and stored in facilities that do not have the expertise and authority. The purpose of this thesis, namely: First, to determine the role of law enforcement in combating the crime of trafficking of hard drugs that are not in accordance with the applicable provisions. Secondly, to know the constraints of law enforcement in combating the crime of trafficking of hard drugs in facilities that do not have the expertise and authority third, to know the constraints menngatasi efforts in law enforcement criminal acts of trafficking of hard drugs in facilities that do not have the expertise and authority in the province of Riau.This type of research is classified in socio-juridical research, because this research author directly conduct research on a study in order to provide a complete and clear picture of the issues examined. This research was conducted at the Center for Food and Drug Administration, while the sample population is overall the parties relating to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews , questionnaire and literature study.From the results, it can be concluded that, First, conduct investigations against perpetrators of trafficking hard drugs in facilities that do not have the expertise and authority. Second, constraints in dealing with law enforcement criminal acts of trafficking of hard drugs in facilities that do not have the expertise and authority, among others; lack of human resources, lack of facilities and pre facilities, lack of coordination with relevant agencies, lack of awareness and concern for the laws of society, and a deliberate disregard the store owner to distribute hard drugs. Third, efforts to overcome such obstacles; improve coordination with relevant agencies, structuring of human resources, improve public services. Brief advice of the author is to optimize the role of the investigator, did a deal with related institutions and improve the dissemination of law about the dangers of prescription drugs without a prescriptionKeywords: Investigator-Combat Role-Distribution